Pengaruh Promosi Terhadap Loyalitas Konsumen Di Suis Butchr Steak House Setiabudhi Bandung - Pilanti Ghaisani, Revi; ., Darsiharjo; Miftah, Reiza (Universitas Pendidikan Indonesia, 2016)
This problem of this research is influence of promotion at Suis Butcher SteakHouse Setiabudhi Bandung. This research is done by promotion that is done whose just be going in two years due to so many competitor Steak House who comes in Bandung. The purpose of this research is to know what is the infulence of promotion program to the loyalty of consumer.Method that used in this research is quantitative method with descriptive method and technique of aggregate data is used field study (observation, interview, assessment) and book study. The assessment is spreaded by 100 respondent of consumer. Technique of analysis data is used validitas test, reliabilitas test and double regression linear concerning the assessment that had spreaded. The result of this research is showed the influence of promotion program to theloyalty consumer at Suis Butcher Steak House Setiabudhi Bandung with the score 84,5%, and 15,5% is explained with other variable in this research. Promotion program whose is dominant that had big influence to loyalty of consumer is sales promotion with the score is 2,074 1,984 and word of mouth dwith score is 4,275 1,984.